Efektifitas Penerapan Bimbingan Kelompok untuk Meningkatkan Pemahaman Siswa tentang Bahaya Pernikahan di SMPN 2 Wae Ri’i Kabupaten Manggarai - Anung, Delvitiana Avila Anung Delvi; Nalle, Andriani Paulin; Masi, Lolang Maria (Prodi Bimbingan Konseling FKIP UNDANA, 2024)
Carrying out marriage before the specified age has risks that can be felt by both men and women, such as dropping out of education, disruption of reproductive health, and divorce at a young age, as well as cases of domestic violence which result in depression which leads to trauma. So there is a need for systematic and effective problem solving by implementing guidance group services to increase students' understanding of the dangers of early marriage at SMPN 2 Wae Ri'i, Manggarai Regency. This research uses a quantitative approach with a pre-experimental research type with a one group pretest and posttest research design. This research was carried out at SMPN 2 Wae Ri'i Manggarai Regency with a population of 300 people and a sample of 12 people. The sampling technique used was the purposive sampling method. The data collection technique uses a Likert scale questionnaire. The data analysis techniques used are descriptive analysis and paired difference test analysis of sample t tests with the help of SPSS For Windows 20Version. The results of the study showed that after being given treatment the difference in the average score before being given treatment was 84.00 and there was a post test average after being given treatment of 157.83. Apart from that, the t count obtained using the paired sample t test was (-57.763) this value was > t table (1.796) with a sig value of 0.00 < 0.05, which means Ha is accepted and Ho is rejected. In this way, group guidance services can be used to increase students' understanding of the dangers of early marriage